Comprehensive assessment of the aortic valve in critically ill patients for the non-cardiologist. Part II: Chronic aortic regurgitation of the native valve - Walpot, Jeroen; Vermeiren, Guy L.; Al Mafragi, Amar; L.N.G. Malbrain, Manu (Anestezjologia Intensywna Terapia, 2021)
Inadequate diastolic closure of the aortic valve causes aortic regurgitation (AR). Diastolic regurgitation towards the left ventricle (LV) causes LV volume overload, resulting in eccentric LV remodelling. Transthoracic echocardiography (TTE) is the first line examination in the work-up of AR. TTE allows quantification of left ventricular end-diastolic diameter and volume and left ventricular ejection fraction, which are key elements in the clinical decision making regarding the timing of valve surgery. The qualitative echocardiographic features contributing to the AR severity grading are discussed: fluttering of the anterior mitral valve leaflet, density and shape of the continuous wave Doppler signal of the AR jet, colour flow imaging of the AR jet width, and holodiastolic flow reversal in the descending thoracic aorta and abdominal aorta. Volumetric assessment of the AR is performed by measuring the velocity time integral of the left ventricular outflow tract (LVOT) and transmitral valve (MV) plane, and diameters of LVOT and MV. We explain how the regurgitant fraction and effective regurgitant orifice area (EROA) can be calculated. Alternatively, the proximal isovelocity surface area can be used to determine the EROA. We overview the utility of pressure half time and vena contracta width to assess AR severity. Further, we discuss the role of transoesophageal echocardiography, echocardiography speckle tracking strain imaging, cardiac magnetic resonance imaging and computed tomography of the thoracic aorta in the work-up of AR. Finally, we overview the criteria for valve surgery in AR.